Um superpoder sem super-herói : licenciamento arqueológico para que(m)? - Melchiades, Carlos Eduardo Ferreira (2022)
This thesis intends to elaborate a discussion on the execution of heritage education projects linked to the archaeological component of environmental licensing. To develop the discussion and raise suggestions, I conduct a historical contextualization of the field, marking its beginning, going through its development, its discussions and its problems, adressing aspects of both the application and the final results of developed projects. Specific issues such as the implication of a division in archaeological science between academics and professionals, as well as the social and political responsibilities of the archaeologists are also adressed, helping the reader to understand the discussions raised. Finally, examples of propositional actions that can serve as inspiration, assembled with the suggestions presented, close the explanation of what I consider an attempt to solve an immediate problem of practice in this field.